In-situ Studies of Microbial CH4 Oxidation Efficiency in Arctic Wetland Soils – Application of Stable Carbon Isotopes - Preuss, Inken-Marie (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2013)
Arctic wetland soils are significant sources of the climate-relevant trace gas methane (CH4). The observed accelerated warming of the Arctic is expected to cause deeper permafrost thawing followed by increased carbon mineralization and CH4 formation in water-saturated permafrost-affected tundra soils thus creating a positive feedback to climate change. Aerobic CH4 oxidation is regarded as the key process reducing CH4 emissions from wetlands, but quantification of turnover rates has remained difficult so far. This study improved the in-situ quantification of microbial CH4 oxidation efficiency in arctic wetland soils in Russia’s Lena River Delta based on stable isotope signatures of CH4. In addition to the common practice of determining the stable isotope fractionation during oxidation, additionally the fractionation effect of diffusion, an important gas transport mechanism in tundra soils, was investigated for both saturated and unsaturated conditions. The isotopic fractionation factors αox and αdiff were used to calculate the CH4 oxidation efficiency from the CH4 stable isotope signatures of wet polygonal tundra soils of different hydrology. Further, the method was used to study the short-term effects of temperature increase with a climate manipulation experiment. For the first time, the stable isotope fractionation of CH4 diffusion through water-saturated soils was determined with αdiff = 1.001 ± 0.0002 (n = 3). CH4 stable isotope fractionation during diffusion through air-filled pores of the investigated polygonal tundra soils was αdiff = 1.013 ± 0.003 (n = 18). For the studied sites the fractionation factor for diffusion under saturated conditions αdiff = 1.001 seems to be of utmost importance for the quantification of the CH4 oxidation efficiency, since most of the CH4 is oxidized in the saturated part at the aerobic-anaerobic interface. Furthermore, it was found that αox differs widely between sites and horizons (mean αox = 1.018 ± 0.009) and needs to be determined on a case by case basis. The impact of ...